math semester 1 unit 2
Solve the equation. 8 - 2x = -8x + 14 x=-1 x=-3/5 x=3/5 x=1
x=1
Which number can each term of the equation be multiplied by to eliminate the decimals before solving? -m + 0.02 + 2.1m = -1.45 - 4.81m 0.01 0.1 10 100
100
Two runners are saving money to attend a marathon. The first runner has $112 in savings, received a $45 gift from a friend, and will save $25 each month. The second runner has $50 in savings and will save $60 each month. Which equation can be used to find m, the number of months it will take for both accounts to have the same amount of money? 112 - 25m + 45 = 50 - 60m 112 + 25 + 45m = 50m + 60 112 + 25 - 45m = -50m + 60 112 + 25m + 45 = 50 + 60m
112 + 25m + 45 = 50 + 60m
Which number can each term of the equation be multiplied by to eliminate the fractions before solving? 6-3/4x+1/3=1/2x+5 2 3 6 12
12
Which number can each term of the equation be multiplied by to eliminate the fractions before solving? -3/4m-1/2=2+1/4m 2 3 4 5
4
Use properties to rewrite the given equation. Which equations have the same solution as 3/5x+2/3+x=1/2-1/5x?Select three options. 8/5x+2/3=1/2-1/5x 18x + 20 + 30x = 15 - 6x 18x + 20 + x = 15 - 6x 24x + 30x = -5 12x + 30x = -5
8/5x+2/3=1/2-1/5x 18x + 20 + 30x = 15 - 6x 24x + 30x = -5
Which step could be used to help isolate the variable in the following equation? 5.6j - 0.12 = 4 + 1.1j Subtract 0.12 from both sides. Subtract 5.6 from both sides. Subtract 4j from both sides. Subtract 1.1j from both sides.
Subtract 1.1j from both sides.
What is the solution to the linear equation? 4b + 6 = 2 - b + 4 b = -2 b = 0 b = 4 b = 6
b=0
What is the solution to the linear equation? d - 10 - 2d + 7 = 8 + d - 10 - 3d d = -5 d = -1 d = 1 d = 5
d=1
What is the justification for the step taken from line 2 to line 3? the subtraction property of equality the multiplication property of equality combining like terms on one side of the equation the distributive property
the subtraction property of equality
What is the solution to the linear equation? 2.8y + 6 + 0.2y = 5y - 14 y = -10 y = -1 y = 1 y = 10
y=10
Solve the equation. y + 6 = -3y + 26 y = -8 y = -5 y = 5 y = 8
y=5